STUDY OF DRUG UTILIZATION PATTERN OF CALCIUM, VITAMIN D SUPPLEMENTS, AND ANTI-OSTEOPOROSIS DRUGS IN PATIENTS WITH OSTEOPOROTIC FRACTURE: A PROSPECTIVE CROSS-SECTIONAL STUDY - Augustine, Angel Maria; Shamrao, Dessai Sneha; Basnet, Sujan; Bhoja, Anchan Namita; Shareef, Javedh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was carried out to assess the drug utilization pattern of calcium, Vitamin D supplements, and anti-osteoporosis drugs in patients with osteoporotic fracture in an Indian teaching hospital. Methods: A cross-sectional study was carried out for 6 months in outpatients receiving treatment from the orthopedic department of an Indian teaching hospital. Demographic details, comorbidities, types of fracture, laboratory parameters, and drug therapy were collected from the patient case records who met the study criteria and documented in the data collection form. All the collected details were later analyzed using descriptive statistics. Results: A total of 73 patient's prescriptions were reviewed, in which 45.2% were male and 54.8% were female. Majority of the patients were in the age group of 50â€“60 years with mean age of 63.52Â±11.06 years. Hypertension (27.16%) was the highest comorbidity identified in the study followed by diabetes (18.51%) and coronary artery disease (14.81%). Of the total patients, 65.75% were prescribed with calcium and Vitamin D supplements and 2.73% received bisphosphonates. Conclusion: The study shows the pattern of drug use in elderly with osteoporotic fractures. Since calcium and Vitamin D are vital for treating osteoporotic fractures, adequate monitoring of serum levels of calcium and Vitamin D3 may help to prescribe doses with desired need and safety level.